Preliminary analysis of the flow field in a transparent model of a SRF cavity by PIV. Issue 1 (July 2021) - Cozzi, F; Pianello, G; Ambros, A D'; Pagani, C; Sertore, D
Abstract: Niobium superconductive radio frequency cavities (SRF cavities) are commonly employed in linear accelerator; very pure, clean, and smooth internal walls are required to make the cavity working properly and with a high Q factor. Typically, to achieve a suitable surface quality the SRF cavities are subjected to a surface treatment called Buffered Chemical Polish (BCP), the latter uses a strong concentrated acids mixture flowing through the cavity to chemically etch a thin niobium layer (∼250 μm). A viable way to understand and optimize the BCP process is by using computational fluid dynamic (CFD); however, the experimental validation of the numerical and physical models is required to confidently use CFD results. The aim of our work is to investigate the fluid dynamics of the BCP process by using the Particle Image Velocimetry (PIV) and the refractive index matching (RIM) techniques, and to provide data to validate CFD simulations. The paper describes and briefly analyse the experimental setup and the preliminary results achieved so far.